Uji Aktivitas Antioksidan dan Anti Aging Body Butter dengan Bahan Aktif Ekstrak Daun Kelor - Nunuk Aries Nurulita; Elza Sundhani; Irma Amalia; Fifi Rahmawati; Nina Nurhayati Dian Utami (JURNAL ILMU KEFARMASIAN INDONESIA, 2019)
Moringa leaf (Moringa oleifera) was one of plants that containt phenol compounds such as alkaloid, tannin, saponin and flavonoid that were useful as a antioxidant and anti aging. The aim of this research was to prove antioxidant and anti aging’s activity of Moringa leaf. The extraction process of Moringa leaf using Maseration method with ethanol solvent 70 % ratio 1:10, then the antioxidant properties determinate using beta carotene bleaching (BCB) and anti aging’s activity test was done, after that formulated the body butter with activeingredient of Moringa leaf extract 0,5 %. Moringa extract contains total phenolic 10,45 mg GAE/g extract and 5,53 % of total flavonoid. The result showed that Moringa leaf extract had inhibition of beta carotene bleaching properties as shown by BCB results. Moringa leaf extract inhibit the collagenase activity until 47,25 % at concentration of 1600 ppm. Moringa leaf extract body butter has high potency of antiaging through antioxidant and collagenase inhibitor mechanism. Moringa body butter had good organoleptic properties. However the physical properties of moringa body butter should be optimozed its composition to get the better one.